Patient navigators facilitating access to primary care: a scoping review. Issue 3 (17th March 2018) - Peart, Annette; Lewis, Virginia; Brown, Ted; Russell, Grant
Abstract : Objective: Patient navigators are a promising mechanism to link patients with primary care. While navigators have been used in population health promotion and prevention programmes, their impact on access to primary care is not clear. The aim of this scoping review was to examine the use of patient navigators to facilitate access to primary care and how they were defined and described, their components and the extent to which they were patient centred. Setting and participants: We used the Arksey and O'Malley scoping review method. Searches were conducted in MEDLINE, Embase, ProQuest Medical, other key databases and grey literature for studies reported in English from January 2000 to April 2016. We defined a patient navigator as a person or process creating a connection or link between a person needing primary care and a primary care provider. Our target population was people without a regular source of, affiliation or connection with primary care. Studies were included if they reported on participants who were connected to primary care by patient navigation and attended or made an appointment with a primary care provider. Data analysis involved descriptive numerical summaries and content analysis. Results: Twenty studies were included in the final scoping review. Most studies referred to 'patient navigator' or 'navigation' as the mechanism of connection to primary care. As such, we grouped the components according to Freeman's nine-principle framework of patient navigation. Seventeen studies included elements of patient-centred care: informed and involved patient, receptive and responsive health professionals and a coordinated, supportive healthcare environment. Conclusions: Patient navigators may assist to connect people requiring primary care to appropriate providers and extend the concept of patient-centred care across different healthcare settings. Navigation requires further study to determine impact and cost-effectiveness and explore the experience of patients and their families.